Regional economic convergence: the case of Latin American Economies - Elías, Víctor (Estudios de Economía, 2016)
The objective of this paper is to study economic regional convergence in Argentina, Brazil, and Peru using the methodology of Barro and Sala-i-Martin. Even though the regional data on those countries are not as rich as needed to fully apply their methodology, it provides a reasonable start in the search of the existence or not of regional convergence and its determinants in Latin America.